Mini-review of application of IoT technology in monitoring agricultural products quality and safety - Ping, Hua; Wang, Jihua; Ma, Zhihong; Du, Yuanfang (International Journal of Agricultural and Biological Engineering, 2018)
Internet of Things (IoT) technology has been identified as one of the emerging technologies in information technology (IT), which is widely used in all walks of life in the world. The key technologies of IoT technology, such as radio frequency identification (RFID), wireless sensor network (WSN), sensors and global positioning system (GPS), had been widely used in farmland and greenhouse management, environmental monitoring, cold chain monitoring and tracking, and traceability, etc. As advancements in science and technology, IoT technology has been widely applied in agricultural products quality and safety, which brought a number of potential benefits for detecting agricultural products easier and automatically, improving the efficiency and speed of operations, decreasing the labor cost, promoting the agricultural products quality and safety. This paper intended to introduce the concept of IoT technology, the key technologies used at present and review the recent applications of IoT technology in monitoring agricultural products quality and safety in the whole industry chain, such as production, processing, circulation, sales and traceability. Challenges and trends of agricultural products quality and safety in the future were also discussed.Keywords: IoT, agricultural products, quality and safety, RFID, WSN, sensors, GPSDOI: 10.25165/j.ijabe.20181105.3092Citation: Ping H, Wang J H, Ma Z H, Du Y F. Mini-review of application of IoT technology in monitoring agricultural products quality and safety. Int J Agric & Biol Eng, 2018; 11(5): 35–45.